A phylogenetic relationship in the genus rhinolophus (family :rhinolophidae) from berneo inferred using partial MtDNA cytochhrome b gene - Besar, Ketol (Universiti Malaysia Sarawak, 2005)
A study on genetic relationship among Rhinolophus species was conducted in Borneo. A total number of thirtytwo individuals from ten species of Rhinolophlls including one species (R. yunenensis) from Thailand were analysed using DNA sequencing technique. A total of nine samples included four samples from Genbank of 409 bp length of sequence were examined. Of the 409 nucleotide positions examined, 149 positions (36.4%) were variable sites and 104 positions (25%) were phylogenetica\ly informative sites. Cyt b mitochondrial DNA was targeted to amplify 450 base pair sequences and phylogenetic relationships were constructed using distance neighbor joining and maximum parsimony analyses. The results showed that genus Rhinolophus is monopheletic, which formed two clusters. Phylogenetis analyses indicated that relationship within Rhinolophus is close ranging 6.8% to 17.8%. Further studies on the genetic relationship should be conduct by using full sequence ofCyt b (1140bp) and five species of Rhinolophus.